Obesity accelerates acute promyelocytic leukemia in mice and reduces sex differences in latency and penetrance. Issue 7 (24th May 2022) - Kincaid, John W. R.; Weiss, Gretchen; Hill‐Baskin, Anne E.; Schmidt, Heidi M.; Omoijuanfo, Ovwoioise; Thompson, Cheryl L.; Beck, Rose C.; Berger, Nathan A.
Abstract: Objective: Obesity has emerged as a prominent risk factor for multiple serious disease states, including a variety of cancers, and is increasingly recognized as a primary contributor to preventable cancer risk. However, few studies of leukemia have been conducted in animal models of obesity. This study sought to characterize the impact of obesity, diet, and sex in a murine model of acute promyelocytic leukemia (APL). Methods: Male and female C57BL/6J.mCG +/PR mice, genetically predisposed to sporadic APL development, and C57BL/6J (wild type) mice were placed on either a high‐fat diet (HFD) or a low‐fat diet (LFD) for up to 500 days. Results: Relative to LFD‐fed mice, HFD‐fed animals displayed increased disease penetrance and shortened disease latency as indicated by accelerated disease onset. In addition, a diet‐responsive sex difference in APL penetrance and incidence was identified, with LFD‐fed male animals displaying increased penetrance and shortened latency relative to female counterparts. In contrast, both HFD‐fed male and female mice displayed 100% disease penetrance and insignificant differences in disease latency, indicating that the sexual dimorphism was reduced through HFD feeding. Conclusions: Obesity and obesogenic diet promote the development of APL in vivo, reducing sexual dimorphisms in disease latency and penetrance.